Omani Folk Literature and Its Impact on Society - Siddig, Omer (Journal of Cultural Analysis and Social Change, 2025)
Omani folk literature represents a living mirror of the cultural and historical identity of Omani society, reflecting its values, traditions, and worldview through various forms such as Nabati poetry, folktales, proverbs, chants, and performing arts. This literature serves as a repository of collective experiences and a medium for documenting the social, political, and economic transformations Oman has undergone throughout the ages. Folk literature has significantly contributed to strengthening social cohesion by embedding moral and religious values and reinforcing intergenerational bonds through the exchange of stories and proverbs that carry profound wisdom and human experiences. It has also played an educational and awareness-raising role, instilling positive principles such as courage, generosity, and solidarity. Moreover, Omani folk literature has had a notable impact on shaping national consciousness and fostering belonging, as it celebrates heritage, maritime and agricultural traditions, and Oman’s historical role in trade and navigation. With the evolution of Omani society, folk literature has remained a vital tool for preserving cultural identity in the face of globalization, as well as a key pillar in academic studies of heritage and anthropology. Therefore, studying Omani folk literature reveals its central role in nation-building, not merely as a cultural luxury but as a fundamental force in shaping the Omani character and safeguarding its cultural legacy.
Keywords: Littérature -- Oman

الخيل في ديوان الشّاعر العماني أبي الفضل (ت 1345 هــ) - البرقاوي, بسام بن بلقاسم (مجلة العلوم الإنسانية (جامعة سبها), 2025)
نهتمّ في هذه الدّراسة بتدبّر قصائد الخيل التي نظمها الشّاعر العماني محمّد بن عيسى بن صالح الحارثي المكنّى بأبي الفضل. وممّا حفّزنا على الاهتمام بهذا الموضوع ندرة الدّراسات التي تصرف الجهد إلى تدبّر وصف الخيل عند هذا الشّاعر وغيره من الشّعراء العمانيين الذين برّزوا في هذا الغرض. ولمّا كان أبو الفضل شاعرا فارسا من فرسان عصره وقائد زمرة الخيّالة في محافظة الشّرقيّة بسلطنة عمان خصّصنا المبحث الأوّل لاستجلاء منزلة الخيل من حياة الشّاعر قبل أن نتدبّرها في شعره وخاصّة في القصائد التي سميّت بـ" الخيليات". وقد تبيّن لنا في ما تبيّن أنّ الخيل سجيّة في وجدان أبي الفضل. فهو قد نشأ عليها وشبّ في بيئة بينها وبين الخيل أسباب وأنساب. ثمّ أتينا بعد ذلك على المدوّنة الشّعريّة فوزّعناها على محورين اثنين: محور لتدبّر خصائص الخطاب الذي يكون فيه الخيل معنى من معاني القصيدة، ومحورًا لتأمّل القصائد التي اقتصر فيها القول على الخيل ولم يجاوزه إلى غيره من المعاني. وبمقاربة إنشائيّة قرأنا نماذج شعريّة أكثرها من قصائد " الخيليات". فخلصنا إلى جملة من النّتائج لعلّ أبرزها أنّ الحارثي كان شاعرا فارسا يسير على خطى المشهورين بنعت الخيل، فيرددّ ما ترسّخ في المدوّنة الشّعريّة التّقليديّة حول الخيل منزلة وصورة. لكنّه في المقابل يأتي في غير قصيدة ببعض ما لم يأت به الأوائل. ومن ذلك أنّه، فضلا عن ذكرها مشتكيا متغزّلا ومفتخرا مادحا وراثيا متألّما وساخرا متهكّما حاورها محاورة طويلة وأنطقها بكلام لم ينطقه بها غيره من الشّعراء.  وهو زيادة على وصفها في ساح المسابقات وفي ما طوّف من برور قد استنفر بعض الشّعراء ليتقارضوا معه القول في شأنها فرسا نبع من غير مثال وسُويَّ على غير منوال وفي شأنه فارسا مغوارا لا يشّق له غبار.
Keywords: Littérature -- Oman

Preserving Omani Intangible Heritage: A Study of Folktale Authenticity and Classification - Akkawi, Aya Walid Fayyad; Rubai'ey, Fatema; Dineen, Gerard (المجلة العلمية لکلية الآداب جامعة أسيوط, 2025)
To prevent Omani folktale heritage from being lost or distorted, especially in the era of globalization and digitization, and since there is no oral documentation of Omani folktales, there is a need to investigate the authenticity of documented Omani folktales published in print and to classify them based on tale-type. This study attempts to document a comprehensive collection of Omani folktales from existing materials published in or translated into English by developing a classification system based on Hasan El-Shamy‘s established tale-type index. Further, the study aims to assess the authenticity of these folktales by investigating Omani cultural markers found in them and identifying potential distortions or adaptations.
Keywords: Littérature -- Oman

القيم التربوية في الحكايات الشعبية العُمانية، الحكاية الشعبية النزوية أنموذجاً - أمبوسعيدي, عبد الله بن خميس; العامري, محمد بن حمود; الجامعية, أمل بنت عبد الله; الحوسنية, هدى بنت علي (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Keywords: Littérature -- Oman

تحولات العماني الأخير: مقاربة سردية لشخصيات رواية رجال من جبال الحجر للروائي سعود المظفر - الراجحية, باسمة بنت سليمان (جامعة نزوى, 2015)
Keywords: Littérature -- Oman

Oman and Sinbad in the tales of the thousand and one nights - Howes Smith, Fleur (Oman: catalogue created for the oman exhibition in de nieuwe kerk, amsterdam, from 17 october 2009 to 18 april 2010, 2009)
Keywords: Littérature -- Oman

بصمات في الأدب العربي - حالو, أحمد عبد المنعم (ذاكرة عمان, 2024)
Keywords: Littérature -- Oman

دراسة عناصر السرد في رواية "الوخز" لحسين العبري - العجمي, إسماعيل بن مبارك بن سالم (مجلة تسنيم الدولية للعلوم الانسانية والاجتماعية والقانونية, 2024)
تعد رواية "الوخز" للكاتب حسين العبري من الروايات العُمانية الهامة التي اهتمت بالجانب السياسي وذلك من خلال التحقيق في موضوع التنظيم السري المحظور الذي كشفته الدولة، ويهدف هذا البحث إلى دراسة عناصر السرد في رواية "الوخز"، وكيفية توظيف عناصر السرد الروائي: الراوي العليم، والشخصية من حيث لغة الرجل المثقف والرجل الشيخ والمحقق، وتقنية الحوار الداخلي والخارجي لدى الشخصيات، والحدث، والوصف. أوردنا أمثلة على عناصر السرد من خلال الرواية.
Keywords: Littérature -- Oman

التفاعل الرمزي في رواية "سيدات القمر" لجوخة الحارثي بنظرية جورج هربرت ميد - Pradani, Sefyra Adienda Putri (2024)
مستخلص البحث رواية "سيدات القمر" (في النسخة الإنجليزية تعرف ب "Celestial Bodies") لجوخة الحارثي نوع من أنواع الرواية التاريخية والاجتماعية، التي تقدم الصورة المتعمقة عن جهود المرأة العمانية في طلب الميزان بين التقليد والتحديث. إن الحضارة العمانية، التي قد تأثرت بالقيم التقليدية والأبوية، بدأت تواجه موجة التحديث، التي تجلب تغييرات في مختلف جوانب الحياة، بما في ذلك دور ومكانة المرأة في السعي لتحقيق الحرية والمعادلة. وراء ذلك، تكشف هذه الرواية أيضًا عن ديناميكيات الأسر والمجتمع في مواجهة التغيير الاجتماعي. يهدف هذا البحث إلى وصف حضارة وحياة المرأة العمانية كما تفسرها مفهوم العقل والذات والمجتمع في رواية "سيدات القمر" لجوخة الحارثي. باستخدام نظرية التفاعل الرمزي لجورج هربرت ميد، يركز هذا البحث على التفاعلات بين الأفراد والمجتمع، مما يؤكد الفهم من وجهة نظر الذات في استخدام الرموز التي تشير إلى المعنى نتيجة تفسيرها. وتظهر نتائج هذا البحث أن هناك ثلاثة مبادئ تظهر في مفهوم العقل، وهي مرحلة الرمز، ومرحلة تفكير المعنى، ومرحلة الإيماءات؛ أربعة مبادئ تظهر في مفهوم الذات، وهي الأنانية، واحترام الذات، والصورة الذاتية، و"I"/"Me"؛ وثلاثة مبادئ تظهر في مفهوم المجتمع وهي ظهور التعاطف والصراع والتجربة. ABSTRACT The novel “Sayyidat al-Qamar” (in the English version known as “Celestial Bodies”) by Jokha al-Harthi is a historical fiction and social realism genre novel that presents an in-depth portrait of the struggle of Omani women in finding a balance between tradition and modernization. Omani civilization, which was once heavily influenced by traditional and patriarchal values, is slowly starting to face the wave of modernization which brings changes in various aspects of life, including the role and position of women in the pursuit of freedom and equality. Apart from offering a picture of individual struggles, this novel also reveals the dynamics of families and communities in facing social change. This research aims to describe the civilization and life of Omani women as interpreted in the concepts of mind, self and society in the novel “Sayyidat al-Qamar” by Jokha al-Harthi. By using the theory of symbolic interactionism by George Herbert Mead, this research focuses on interactions between individuals and groups which emphasizes understanding from the subject's point of view in using symbols that indicate meaning as a result of their interpretation. This research results show that there are three principles that emerge in the Mind concept, namely the symbol stage, meaning thinking, and gesture stage; four principles that appear in the concept of Self, namely ego, self-esteem, self-image, and “I”/”Me”; and three principles that emerge in the concept of Society, namely the emergence of sympathy, conflict and experience. ABSTRAK Novel “Sayyidat al-Qamar” (dalam versi Inggris dikenal sebagai “Celestial Bodies”) karya Jokha al-Harthi merupakan sebuah novel bergenre fiksi sejarah dan realisme sosial yang menyajikan potret mendalam perjuangan wanita Oman dalam mencari keseimbangan antara tradisi dan modernisasi. Peradaban Oman, yang dulunya sangat dipengaruhi oleh nilai-nilai tradisional dan patriarkial, perlahan mulai menghadapi gelombang modernisasi yang membawa perubahan dalam berbagai aspek kehidupan, termasuk peran dan posisi wanita dalam mengejar kebebasan dan kesetaraan. Selain menawarkan gambaran terkait perjuangan individu, novel ini juga mengungkapkan dinamika keluarga dan komunitas dalam menghadapi perubahan sosial. Penelitian ini bertujuan untuk mendeskripsikan peradaban serta kehidupan wanita Oman yang terinterpretasikan dalam konsep pikiran (Mind), diri (Self), dan masyarakat (Society) dalam novel “Sayyidat al-Qamar” karya Jokha al-Harthi. Dengan menggunakan teori interaksionisme simbolik oleh George Herbert Mead, penelitian ini berfokus pada interaksi antar individu maupun kelompok yang menekankan pada pemahaman dari sudut pandang subjek dalam menggunakan simbol-simbol yang menunjuk makna sebagai hasil interpretasinya. Hasil penelitian ini menunjukkan bahwa terdapat tiga prinsip yang muncul dalam konsep Mind, yaitu tahap simbol, pemikiran makna, dan tahap gestur; empat prinsip yang muncul dalam konsep Self, yaitu ego, harga diri, citra diri, dan “I”/”Me”; dan tiga prinsip yang muncul dalam konsep Society, yaitu munculnya simpati, konflik, dan pengalaman.
Keywords: Littérature -- Oman

كتاب "أثير" الشعري : مختارات من الشعر العماني المعاصر = Livre des poèmes d'Atheer: sélection des poèmes omanais contemporains - ولد العروسي, الطيب; Rabīʿī, ʿAbd al-Razzāq (بيت الغشام, 2019)
Keywords: Littérature -- Oman

Reading Ancient Folk Literature the Omani Story of “Abu Qahifa” Is an Example - Siddig, Omar Ahmed; Siddig, Babikir Eltigani; Elmahi, Abdallah (Journal of Social Science and Humanities Research, 2024)
The research deals with a popular tale from the ancient Omani heritage. In our research, we tried to learn about the Omani heritage and the distinct Omani culture, especially its literary heritage. We dealt with the story with literary criticism and analysis, and we focused on the characters of the story, the method of narration, the language, the presentation, the quality of the wording, the artistic plot, the fertile imagination, and the idea that derived its roots from the Omani culture and imagination. In our research, we followed the descriptive and analytical approach that is consistent with the subject of the folk tale.
Keywords: Littérature -- Oman

The conflict between tradition and feminism in Oman (Case study: Al-Tawaf Haith Al-Jamar) - Amin Moghaddasi, Abolhasan; Afzali, Ali; Bigdeli, Narges (Woman in Development & Politics, 2024)
Introduction:The starting point of female criticism coincides with liberation from the linear stereotypes of men's literary history. Feminist literary criticism does not mean to eliminate the differences in the way of writing between women and men, and in this type of criticism, gender differences do not become meaningless, but the purpose of this criticism is to understand women's writing in order to reach a broader perspective of women's reality. In the 19th century, novel writing was considered a purely masculine practice, and mentioning a female novelist caused suspicion, shame, surprise, and misogyny towards the author. The intellectual endeavors of women in less than two hundred years, has opened up new perspectives on human knowledge and raised many important questions. But the astonishing variety and conflict of ideas themselves has become a barrier to understanding how and why they are. Feminist critique examines the role of women in the two axes of the creator of the work (the woman as the writer) and the created personality (the face presented by the woman in the works of the authors). The experience of writing a novel is considered one of the modern literary experiences in the Sultanate of Oman, and its history does not exceed a few decades. The Al-Tawaf Haith Al-Jamar is considered the first women's novel in Oman and its protagonist in life is a kind of victim of patriarchy. The first appearance of women in the field of Omani novel writing took place in 1999 with the novel Al-Tawaf Hayat al-Jamar by Badria Al-Shihhi. Methodology:In this study, the authors try to use the feminist approach and descriptive analytical method to examine the characters of the story and put their actions according to the characteristics of each of the stages of imitation, protest and self-discovery in the classification of feminist criticism and the evolution Identify and analyze them in each of these stages and seek to find answers to these questions: What are the most obvious feminist components in Al-Tawaf Haith Al-Jamar’s novel? Results:Omani novelist Badria Al Shهhhi, in her novel “Al-Tawaf Hayat al-Jamar,” shed light on an important historical stage in the history of her country, which was characterized by the Omani presence in Zanzibar, Africa, and how rebellious movements were raging in several hotspots there, warning of the occurrence of disasters that would cause historical tragedies. In parallel, it monitors a number of social, commercial and economic transformations that interacted and exploded in ways that were not devoid of cruelty and brutality through its characters, which are decorated with contradictions and contradictions. It does not philosophize much in trying to understand the changes that are sweeping it, but rather goes with the waves as if it were part of the movement of the scene with its confusions, strangeness and madness. Badria Al-Shihhi is the first Omani female novelist, and ironically, her first novel is also a feminist novel that, after forty years of silence, steps into the field of literature not to imitate men, but to shout and protest. Widowed at a young age, Zahra finds herself being forced into a hasty marriage to her cousin. Having been conditioned by her family and society to perennially obey society’s diktats, taking destiny into her own hands seems nigh impossible. Her radical decision to do so takes her on the journey of discovery from an Omani village perched atop a mountain to the East African coast. But of more importance than her physical journey through space is her internal one: of how far Zahra has to go to be free from the shackles of discrimination to finally find her place in the world, and what that search for independence holds for her. The findings of the research show that components such as protest, self-expression, violence, suppression of female instinct, taboo breaking have the most contribution in this novel and make it a part of feminist works. Although traces of self-awareness can be seen in this novel, by choosing to isolate the hero, the author has deprived him of reaching the stage of turning inward and self-discovery to find an individual identity and away from any imitation and protest.Conclusion:Al-Tawaf Haith Al-Jamar presents a model of a woman's efforts to liberate herself and not accept outdated patriarchal traditions. The revolution of this woman against the patriarchal society was parallel to the revolution of the African people against the Arabs who invaded their country and took over their lives and property. The author depicts the hardships that this woman endured on the way to achieving her dreams, as well as the financial and life losses that the African people suffered to realize their freedom; It seeks to prove that no freedom comes without a cost. The name he chose for this novel also indicates its content, because tawaf means an endless cycle and sequence that shows the continuation of this struggle. This novel was written in protest against male writing standards and the presentation of a stereotypical image of women, and it prioritized the defense of women's rights and women's idealism. Badria al-Shihhi shows the emergence of self-hiding in a woman named Zohra after enduring the sufferings that have been imposed on her for three decades in her life; shows. A woman whose whole life is described as endless service. Now looking for a range to be heard and seen and discovered; becomes Badria al-Shihhi has used this character as a model for a better and ideal being. In this novel, there is only one woman who is on a ship as a small community and on a path whose limits and end are unclear and all the passengers are men; is in motion The plurality of men in the novel shows the majority of their determining presence in the real society and the fact that there is only one woman among them has a directional and appropriate link with the reality of women being in the minority and describes the society's inferior view of women. Badria al-Shihhi did not accept the silence and description compatible with the environment and used literature as a means to depict the oppression and oppression of women. He leads his protagonist towards self-awareness, but at the end of the novel, by dragging him into isolation and transsexuality, he has deprived him of reaching the stage of turning inward and self-discovery to find an individual identity and away from any imitation and protest.
Keywords: Littérature -- Oman

Écrire l’esclavage au féminin : une étude du roman contemporain omanais - Safar, Jihan (Esclavages & Post-esclavages. Slaveries & Post-Slaveries, 2024)
Cet article traite de l’esclavage et du genre dans la fiction contemporaine omanaise écrite par des femmes. Face au vide historiographique et anthropologique sur l’esclavage légal dans la péninsule Arabique, la littérature nourrie par la mémoire permet d’aborder cette question. Elle rend visible des subjectivités d’esclavisé·es ou de leurs descendant·es absentes des récits dominants. Dépassant les polémiques sur l’usage de la production littéraire dans les sciences sociales, l’article considère la littérature comme un point d’entrée anthropologique, politique et économique apte à éclairer les situations concrètes de l’esclavage et du post-esclavage dans la société contemporaine omanaise. Il souligne tout particulièrement les tensions entre l’écriture mémorielle de l’esclavage et les positions de pouvoir et de genre des écrivaines. Il analyse ainsi une double subjectivité : celle des protagonistes femmes dans le roman et celle des romancières. Deux principaux romans omanais examinent l’esclavage dans la sphère intime et privée de la famille, du mariage et de la sexualité : Sayyidāt al Qamar (Les Corps célestes) de Jokha Alharthi et Al ashyā’ layssat fi amākiniha (Things are not in their place) de Huda Hamed (Al Jahouri). Le premier roman aborde frontalement l’esclavage et la traite omanaise qui s’étendait des côtes d’Afrique orientale jusqu’au Baloutchistan ; la concubine Zarifa étant l’un des principaux personnages. Le second roman raconte l’évitement matrimonial entre Amal, une baysara (métissée) et Mohsin, un « Arabe » issu d’une tribu « noble » et « pure ». Dans les deux romans, la question de la race, du genre et de l’origine généalogique s’inscrit au cœur des pratiques matrimoniales, sexuelles et familiales.L’article s’appuie sur une enquête de terrain menée au sultanat d’Oman en février 2023. Des entretiens en langue arabe ont été conduits avec les deux romancières Jokha Alharthi et Huda Hamed, afin de recueillir leurs discours et leurs perceptions sur le passé colonial, sur l’esclavage et son héritage, sur le rôle de la littérature, sur la réception de leur œuvre par le public local et international ainsi que sur les sources utilisées dans leur production littéraire. D’autres entretiens ont été menés avec des personnalités littéraires, académiques, et des représentants officiels.Dans la première partie de cet article, le roman contemporain est traité comme un matériau permettant de saisir les transformations sociétales dans le sultanat d’Oman en contexte d’esclavage et de post-esclavage, dans une perspective intersectionnelle. En premier lieu, cette partie met en lumière les multiples formes de domination au sein de l’institution du concubinage, soulignant la notion de propriété légale de l’esclave (milk) dans la loi musulmane. Elle montre le cycle de violences sexuelles exercées sur le corps de l’esclave-femme ainsi que les relations complexes entre maître et concubine où se mêlent abus, affection et domination. Elle témoigne aussi des relations prohibées entre la maîtresse et son esclave. Cette première partie indique également comment le roman permet d’évoquer les expériences de genre différenciées parmi les esclaves eux-mêmes, entre les esclaves né·es dans la maison du maître et les esclaves capturé·es qui se remémorent le « voyage ». Une telle distinction informe sur le sentiment d’appartenance à la nation : la loyauté nationale semble plus forte parmi les esclaves né·es dans la maison du maître, notamment les femmes, qu’au sein de la génération capturée, surtout masculine, bien plus rebelle. Le roman contemporain omanais donne l’opportunité, en troisième lieu, de décrire les pratiques post-esclavagistes au sein du mariage, un lieu de reproduction des hiérarchies sociales et raciales. Il évoque le thème des évitements matrimoniaux qui exprime des subjectivités féminines où s’entrecroisent race, genre et lignée. Prenant le cas des bayāsir (métissé.es), le roman omanais révèle que la discrimination ne relève pas de la couleur de peau mais de la généalogie. Si ces romans rendent visibles des trajectoires et des expériences d’esclavisé·es, le positionnement des romancières peut sembler paternaliste, les femmes noires étant souvent associées aux stéréotypes liés à la prostitution et à l’impossibilité pour elles de former une famille stable.La deuxième partie de l’article aborde les modes de narration, les positionnements des romancières omanaises, et la réception controversée de l’œuvre littéraire évoquant l’esclavage. Elle traite des subjectivités et des sources utilisées par les romancières. La place attribuée à l’histoire orale et aux archives dans la construction romanesque est centrale dans l’écriture féminine et mémorielle sur l’esclavage. Des subjectivités racialisées sont également évoquées. À l’inverse des black feminists afro-américaines qui ont écrit des neo-slave narratives, les romancières omanaises ne sont pas issues de communautés afro-arabes descendantes d’esclaves ; elles appartiennent à la classe dominante et « blanche ». Si ces romancières sont accusées de faire le jeu du colonialisme, on leur reproche également d’être son relais. Des attaques féroces ont fusé après l’attribution de prix littéraires (comme celui du Man Booker International Prize 2019 pour Sayyidāt al Qamar de Jokha Alharthi) et la traduction de leur œuvre. Pour les « conservateurs », ces romans montraient les Omanais sous l’angle des colonisateurs ou des esclavagistes. Ainsi, la traduction de ces œuvres a produit des discours locaux autour de l’esclavage et a soulevé de nombreuses polémiques à propos de la mémoire coloniale. Cette fictionnalité vient combler un silence institutionnel, les autorités évitant d’engager un débat national sur l’esclavage qui pourrait nuire à l’image internationale du pays. Au-delà d’un récit national homogène, la fiction contemporaine, essentiellement écrite par des femmes, permet donc de rendre visible l’esclavage dans la péninsule Arabique. Dépassant des visions sur l’esclavage oriental « doux » et « bienveillant », cet article cherche à inscrire celui-ci dans les études sur les histoires globales de l’esclavage.
Keywords: Esclavage -- Oman; Littérature -- Oman

Black magic and djinn in Omani literature: examining the myths and reality - Hosni, Manar al- (Arab and Muslim Science Fiction: Critical Essays, 2022)
Keywords: Littérature -- Oman

Power, Narrative, and Magical Realism in Hudā Ḥamad’s Sindrīllāt Masqaṭ - Aljomaa, Mervat (Journal of Arabic Literature, 2023)
This article examines the narrative and literary techniques employed in Hudā Ḥamad’s Sindrīllāt Masqaṭ to draw on Omani women’s experiences of writing and speaking as sources of empowerment and narrative identity. Marking a shift from the dominant realistic and historical fiction often associated with male writers, Ḥamad experiments with magical realism, the carnivalesque, intertextuality, and metafiction to reconfigure the novelistic genre beyond the national prescriptions of literary production. Through the voice of the narrator, alongside the voices of other ordinary women, the novel underscores the significance of women’s symbolic practices within the societal and cultural boundaries of Oman. In an allegory of writing—a major thread running throughout the novel—the narrator/writer seeks to combine the composite, multiple, and fictional fragments of various women’s stories into a single readable text that preserves oral and cultural memory. Thus, on the one hand, this article explores the writer’s experimentation with narrative and storytelling within the context of the Omani literary tradition. On the other hand, it examines modes of women’s empowerment that work through articulative and enunciative practices in the face of linguistic frustration.
Keywords: Littérature -- Oman

Counterproxy: Sonallah Ibrahim’s Warda and the revolution in Oman - Rasberry, Vaughn (Representations, 2023)
Keywords: Littérature -- Oman

تمثّلات "الحواريّة" وجماليتها في رواية "همس الجسور" لـ "علي المعمريّ" - الشرجي, علي بن شافي بن علي (مجلة الاندلس للعلوم الانسانية والاجتماعية, 2024)
Keywords: Littérature -- Oman

From old to modern socio-cultural transformation in Oman in the novel of Sayyidātul Qomar by Jukhah Al-Hāriṡy - Laluhun, Putri (Journal of Religion and Linguistics, 2024)
This study aims to describe the aspects of socio-cultural transformation from old to modern and to explain the process of socio-cultural change in Oman through Sayyidātul Qomar's novel by using a socio-cultural approach and socio-cultural theory by Koentjaningrat. The object of this research is the novel Sayyidātul Qomar by Jukhah Al-ḥāriṡy, which was published by the publisher Dār al-Ādāb in 2010 in Beirut, Lebanon. The method used in this research is a descriptive qualitative method using data collection techniques in the form of a literature study. The results showed that the aspects of socio-cultural transformation that occurred in Oman in the novel were the religious/belief system, society, education/knowledge, economy, government and technology, and life equipment. The process of socio-cultural transformation from old to modern is divided into two, namely, the driving factors for the transformation and the problems/conflicts in the transformation process. These driving factors include political factors (changes in the power system), economic crises (trade crises), feminism (women's struggles for their rights as women), and open society systems (birth of new generations). These problems/conflicts include the conflict between science and the supernatural, the rebels and the Omani government, the human world and the Jinn, and the enslaver and enslaved person.
Keywords: Littérature -- Oman

Developmental Structuralism in the Story of "Abur sekak Al-hāra wa nāī fī jabī" by Omani author Hamad al-Mukhinī based on Lucien Goldman's theory - Deris, Athra; Pourabed, Mohammad Javad; Zare, Naser; Balavi, Rasoul; Khezri, Ali (Arabic Literature, 2024)
Developmental Structuralism in the Story of 'Abur sekak Al-hāra wa nāī fī jabī' by Omani author Hamad al-Mukhinī based on Lucien Goldman's theory Abstract Sociology is a science that studies human societies and how they are affected by events. The relationship between literature and society is a reciprocal one in which literature is influenced by society and vice versa. The sociology of literature has undergone many changes since its inception and one of the theories that has contributed to this transformation is theories (Lucien Goldman's developmental structuralism). There are many writers who paid attention to their societies and its events, and the Omani writer Hamad al-Mukhinī did not shy away from the issues of his society, but addressed them in his texts. The present study, following the critique of the developmental structuralism of the story 'Abur sekak Al-hāra wa nāī fī jabī', has adopted a descriptive-analytical approach and examine the components of this theory in the story. The most important axes that the research reached results in, including: The story worldview is revealed through the possible consciousness of the narrator/young person, in a way, he was pursuing his dream and realizing it, although he had opponents in this way. In addition to the issues that the author has considered in the course of the story, Social customs and traditions affecting the behavior of social groups, domestic violence Or father against wife and child and superstitions.
Keywords: Littérature -- Oman

الرسالة الحضارية للأدب العماني - فارس, وليد فكري; الزهيمي, صالح بن سليمان; الشيباني, سلطان بن مبارك (ذاكرة عمان, 2017)
Keywords: Littérature -- Oman

Literature in Oman During the Reign of Sultan Qaboos - Michalak-Pikulska, Barbara (Sultan Qaboos and modern Oman, 1970-2020, 2022)
Keywords: Littérature -- Oman

فضاءات الأدب العماني الحديث ‏ابحاث واقراءات و مراجعات - السمرائي, فليح مضحي (الجمعية العمانية للكتاب, 2023)
Keywords: Littérature -- Oman

رحلة بتوقيت نيويورك - الوهيبي, بدر بن ناصر (الجمعية العمانية للكتاب, 2023)
Keywords: Littérature -- Oman

De l’exil à l’appareil d’État : trajectoires élitaires des « pionniers » de la modernité littéraire omanaise - Ayachi, Mehdi (Arabian Humanities, 2022)
La modernité littéraire et intellectuelle omanaise débute bien avant la nahḍa du sultan Qabous b. Said (r. 1970-2020), dont il s’agit de réévaluer la pertinence pour une histoire intellectuelle du Sultanat d’Oman. C’est plutôt sous le règne de Sa‘îd b. Taymûr (r. 1932-1970) que s’amorcent des changements – dans les pratiques d’écriture et les sociabilités littéraires – à l’origine de l’émergence de cette nouvelle figure de la modernité qu’est l’intellectuel (al-muthaqaf). On se propose ici d’étudier quelques moments-clés de la trajectoire historique de l’élite éduquée sous Sa‘îd, depuis son exil dans les pays voisins du Golfe et du Machrek à la recherche de nouvelles opportunités éducatives et professionnelles jusqu’à son retour et son intégration à l’État en 1970, à l’appel du sultan Qabous. On posera ainsi la question de la place des intellectuels au sein de cette élite éduquée et de leur rôle dans l’élaboration de projets nationalistes qui en font le seul groupe capable de renverser le sultan et de gouverner le pays. L’histoire de cette génération, dont les membres sont parfois qualifiés de « pionniers » (rawâd) de la modernité littéraire omanaise, mettra ainsi en lumière l’insertion précoce d’Oman dans le moment panarabe et anticolonialiste des décennies 1950-1960.
Keywords: Littérature -- Oman

خطاب الآخر فى الأدب المروى : الأنثى فى الحكاية العمانية أنموذجا - الدرمكي, عائشة بنت حمد بن سعيد (مجلة الخليل للدراسات الأدبية واللغوية, 2014)
إن مفهوم (التواصل الشعبي) يحيل على الظواهر التواصلية التي تنبني على نية التبادل الرمزي في إطار فضاءات شعبية متعددة، وانطلاقا من التصور لعملية التواصل اللساني والمجتمعي، فإن مادة التواصل هنا هي تلك الأنساق اللغوية التي تشكل موضوعا للسانيات والسوسيو لسانيات والتداوليات وهي أنساق تهدف إلى التواصل مع الآخر باعتباره متلقيا للرسالة (النص). إن الاتجاه الحديث الذي اتخذته نظرية التلفظ في تحليل أفعال الخطاب قد لا يمثل تجديدا جذريا في تحليل الخطاب إلا أن هذه النظرية تعطي حياة جديدة لمفارقة يعرفها الكلاسيكيون وهي تنتج التنافس في الملفوظ الواحد بين الهدف التمثيلي لشيء بعينه، وما كانت قواعد بور رويال تدعوه (الانعكاس أو التفكير بالقوة أو المحتمل). إن خطاب المجتمع إما أن يكون عاما (بصيغة الرجل)، أو خاصا (بصيغة المرأة)، وهذه العمومية أو الخصوصية، إنما تعكس خبرة المجتمع وموسوعيته المعرفية في إطار التواصل مع ذواته (الأنا والآخر) (الذكر والأنثى)، ولعل التراث الثقافي الشفاهي بوصفه أنساقا مجتمعية يقدم في ذلك خطابا متمايزا من حيث العلامات اللسانية والنسقية والمقامية التي تعج بها نصوصه، وعلى ذلك فإن هذا البحث هو محاولة لتحليل الخطاب الذي يتجه إلى الآخر (الأنثى)، في نص التراث الثقافي في عمان، للوصول إلى الكشف عن هوية الأنثى في الثقافة المجتمعية، وسيكون التحليل خاصا لنصوص التراث الأدبي الشعري والنثري في عمان من خلال تحليل نماذج منه، وذلك بتحليل أفعال الخطاب للتعريف بطريقة مساهمة هذه النظرية في التعريف بعلامات الخطاب وتحديد نوع الذات الفاعلة التي تظهر خلال النص وعليه ستكون محاور البحث كالآتي: المحور الأول: المكون التركيبي لخطاب الآخر في النص الشفاهي. المحور الثاني: قدرة (فعل الإرادة) في المكون الخطابي للآخر في النص الشفاهي. المحور الثالث: الموسوعة المجتمعية والتنظيم الخطابي في بنيات خطاب النص الشفاهي.
Keywords: Littérature -- Oman

Contemporary Omani Literature and the Journeys to Horizons: A Reading in the Themes of Epistemological Departure - Kindī, Muḥsin (The 9th Conference on Ibadi Studies: China and the World: Development and Cooperation from the Perspective of the Belt and Road Initiative, 2018)
Keywords: Littérature -- Oman

النمير: حكايات وروايات - السيفي, محمد بن عبد الله (مكتبة و تسجيلات غاية المراد, 2015)
Keywords: Littérature -- Oman

Dhafari Folklore and Folktale = الفلكلور والروايات الشعبية في ظفار - Johnstone, Thomas Muir (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Littérature -- Oman

دراسات في أدب عمان والخليج - اليحيائي, شريفة خلفان; ميدان, أيمان (دار المسيرة, 2004)
Keywords: Littérature -- Oman

تجليات المكان والزمان في القصة العمانية القصيرة - ميدان, أيمان (دراسات في أدب عمان والخليج, 2004)
Keywords: Littérature -- Oman

The contemporary Omani novel and changing reality - Allawati, Ehsan Sadiq (Giornata di studio su Storia e Cultura dell’Oman, 2021)
Keywords: Littérature -- Oman

Folktales from the Arabian Peninsula: tales of Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, the United Arab Emirates, and Yemen - Taibah, Nadia Jameel; MacDonald, Margaret Read (World folklore series, 2016)
Keywords: Littérature -- Oman

Social, historical and political subjects in the modern Omani short story - Michalak-Pikulska, Barbara (Studies in Arabic and Islam: proceedings of the 19th Congress: Halle 1998, 2002)
Keywords: Littérature -- Oman

L’énigme du Maydān : présentation d’un genre poétique omanais - Audebert, Claude; Bakhouch, Mohamed (Chroniques yéménites, 2015)
Keywords: Littérature -- Oman

Omani proverbs - Jayakar, A. S. G. (Oleander, 1986)
Keywords: Littérature -- Oman

References to Oman in the literature on Arabian geography - Martin, Manuela (Journal of Oman Studies, 1983)
Keywords: Littérature -- Oman

Omani proverbs: problems in translation - Emery, Peter J. (New Arabian Studies, 1997)
Keywords: Littérature -- Oman

Contemporary poetry in Oman - Michalak-Pikulska, Barbara (Modern Oman: studies on politics, economy, environment and culture of the Sultanate, 2006)
Keywords: Littérature -- Oman

Folklore and folk literature in Oman and Socotra - Johnstone, Thomas Muir (Arabian Studies, 1974)
Keywords: Littérature -- Oman

Le avventure di Ḏiyāb e Abū Zayd. Racconto hilaliano del Dhofar (Oman) - Canova, Giovanni (Quaderni di Studi Arabi, 2018)
Keywords: Littérature -- Oman

Modern poetry and prose of Oman, 1970-2000 - Michalak-Pikulska, Barbara (The Enigma Press, 2002)
Keywords: Littérature -- Oman

Religious Aspects in the Poetry of Abū Muslim al-Bahlānī - Michalak-Pikulska, Barbara (Oman, Ibadism and modernity, 2018)
Keywords: Littérature -- Oman

‘The Sindbad Story’ as a Part and Projection of the Omani Identity - Rezvan, Efim (Local and global Ibadi identities, 2019)
Keywords: Littérature -- Oman